2002
DOI: 10.1007/s00497-002-0150-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cell division and expansion in developing petals of Petunia hybrida

Abstract: The definition of the patterns of cell division and expansion in plant development is of fundamental importance in understanding the mechanics of morphogenesis. By studying cell division and expansion patterns, we have assembled a developmental map of Petunia hybrida petals. Cycling cells were labelled with in situ markers of the cell cycle, whereas cell expansion was followed by assessing cell size in representative regions of developing petals. The outlined cell division and expansion patterns were related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 21 publications
2
53
0
3
Order By: Relevance
“…Petunia petals are composed of limb and tube, which are equivalent to blade and claw, respectively, in Eustoma petals. Reale et al (2002) Abaxial epidermal cells were elongated in shape at all stages (Fig. 4), suggesting that cell shape is largely determined at a very early stage of floral development.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Petunia petals are composed of limb and tube, which are equivalent to blade and claw, respectively, in Eustoma petals. Reale et al (2002) Abaxial epidermal cells were elongated in shape at all stages (Fig. 4), suggesting that cell shape is largely determined at a very early stage of floral development.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, it is unclear whether cell division and expansion progress simultaneously at various petal parts. Reale et al (2002) investigated cell division of petals by in situ hybridization using two markers, cyclin and histone 4 genes, during flower development in petunia. They showed that cell divisions are uniformly distributed throughout the petal initially and decline gradually, starting from the basal part (Reale et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In leaves, PhEXP1 mRNA levels were very low, and in anthers, the transcript levels were barely detectable ( Figure 1B). A developmental map of P. hybrida petals previously has been defined that describes the patterns of cell division and expansion throughout 14 different developmental stages (Reale et al, 2002). During the first three stages of petal development, growth is sustained by cell divisions that are uniformly distributed in the apical and basal portion of the petal.…”
Section: Phexp1 Is Preferentially Expressed In Petal Limbsmentioning
confidence: 99%
“…In a previous study, we defined a developmental map of Petunia hybrida (petunia) petals by analyzing the expression of in situ cell cycle markers and by reconstructing the pattern of cell expansion through measurement of cell size (Reale et al, 2002). During flower development, floral organs typically assume their final shape long after the major mitotic activity has ceased, indicating that cell expansion plays an important role in determining organ shape (Pyke et al, 1991;Tsuge et al, 1996).…”
Section: Introductionmentioning
confidence: 99%